The Effect of Physical Activity on Diabetes Mellitus Patients with Hypertension - Dieni Utami, Nisa; Safitri Dyan Kusumaningrum, Niken (KnE Life Sciences, 2021)
Physical activity plays an important role in controlling blood glucose levels and reducing the risk of cardiovascular disorders in patients with diabetes mellitus (DM). DM patients should follow the principle of FITT (frequency, intensity, type and time) while doing a physical activity, which has a direct effect on their health condition. However, the identification of physical activity in DM patients with hypertension is still limited. Therefore, this study aimed to describe the effect of physical activity on DM patients with hypertension. Accordingly, this cross-sectional study included patients with hypertension, aged 18–65 years, able to communicate verbally, and visiting a public healthcare centre in Semarang between February and March 2020. The Baecke Physical Activity Questionnaire (BPAQ) was used to identify the physical activities done by the participants. Quantitative data analysis revealed the distribution of frequency, percentage, mean, and standard deviation. A total of 150 respondents participated in the study, mostly in late adulthood (54.7%), women (68%), and having DM with hypertension for one–five years. The results showed that 40.7% of the respondents had a low level of physical activity, of which 46% did not play any sport and 92.7% had low occupational physical activity. The average leisure time index was 2.31 ± 0.6, which means that most of them did a few physical activities during leisure time. It is concluded that since many DM patients with hypertensions were categorized as having low level of physical activity, this may affect their blood glucose level and blood pressure. Keywords: blood glucose, blood pressure, diabetes mellitus, hypertension, physical activity